2009
DOI: 10.1111/j.1465-3362.2009.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole‐induced Torsade de Pointes in a patient receiving methadone substitution therapy

Abstract: Implication: This cardiac arrhythmia was most likely due to drug interaction between methadone and itraconazole because the patient presented with no other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Itraconazole, an antifungal pharmacological agent, has been reported to cause long QT and TdP in patients receiving terfenadine and also in patients undergoing methadone substitution therapy . Unfortunately, we were unable to test this interaction in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole, an antifungal pharmacological agent, has been reported to cause long QT and TdP in patients receiving terfenadine and also in patients undergoing methadone substitution therapy . Unfortunately, we were unable to test this interaction in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Noorzurani et al 117 reported that a 44-year-old woman who was admitted following an episode of chest discomfort and syncope had been receiving 120 mg of methadone daily for the past nine months, and had consumed 200 mg of itraconazole, prescribed the day before. Her ECG (electrocardiogram) showed a QT c interval of 520 ms leading to torsade de pointes, which resolved spontaneously.…”
Section: Itraconazolementioning
confidence: 98%
“…Rhabdomyolysis has been reported in patients on the combination of itraconazole and statins [ 36 ]. Prolonged QTc interval leading to Torsade de points has also been reported when co-administered with methadone [ 37 ] and terfenadine, but not the newer antihistamines [ 38 ]. Treatment will often require adjustments to the non-azole treatment and switching to a non-CYP3A4 metabolised alternative.…”
Section: Treatmentmentioning
confidence: 99%